Characteristics of spatial use and importance of landscape features for recovering populations of Eurasian lynx (Lynx lynx) - Hubert Potočnik; Jaka Črtalič; Ivan Kos; Tomaž Skrbinšek (Acta Biologica Slovenica, 2020)
Following the extirpation from Central and Southeastern Europe by the end of the 19th  century, Eurasian lynx (Lynx lynx) was reintroduced in the Alps and Dinarics. The recovering population sizes fluctuated over the years; however, they remained relatively small and isolated since their distribution after the establishment has not significantly expanded by natural colonization. One of the most radical changes to the landscape of Europe over the past centuries has been the creation of vast urban and agricultural areas and subsequent extension of infrastructure, causing increasingly fragmented landscape, especially for weak dispersers like lynx. There is a pressing need to establish greater connectivity between the genetically isolated populations, particularly throughout the Alps and Dinarics, to achieve a viable metapopulation structure. In the paper, we review scientific knowledge on Eurasian lynx spatial requirements and behaviour, and critically evaluate the methods used. Apart from habitat suitability and connectivity studies, we also provide a review of lynx home range sizes and movement activity, including dispersion. We present habitat suitability model constructed to examine suitable habitat for recovering Dinaric - SE Alpine population and compare home range sizes of lynx from Dinarics in Slovenia with other lynx populations in Europe. Future considerations for lynx conservation should include the impact of climate change, protection of corridor areas, reducing impact of barriers and, if needed, “complement” dispersal via translocations to achieve viable pan-European lynx metapopulation in the future.